The Lancashire Giant: David Shackleton, Labour Leader and Civil Servant - Spencer, Bruce (Labour / Le Travail, 2002)
The article reviews the book, "The Lancashire Giant: David Shackleton, Labour Leader and Civil Servant," by Ross M. Martin.
Keywords: 20th century; Business And Economics--Labor And Industrial Relations; History; History--History of North And South America